Transvaginal prolapsed submucosal leiomyoma after cesarean section misdiagnosed as bladder prolapse: A case report with literature review - Li, Ling; Shen, Jihong; Gao, Zhenhua; Wang, Xingqi; Tian, Daoming; Yang, Xunguo; Zhou, Hang; Li, Bailuan; Tang, Dan; Zhang, Quan (Frontiers in Surgery, 2023)
Uterine leiomyomas are the most common benign tumours that can be found in the female reproductive system. Transvaginal prolapsed submucosal leiomyomas are rare complications of uterine fibroid during the postpartum period. Due to a lack of sufficient published evidence of these rare complications and their uncommon appearance, they often result in diagnostic and treatment difficulties for clinicians. In this case report, a primigravida with no special prenatal examination developed recurrent high fever and bacteraemia following an emergency caesarean section. Vaginal prolapsed mass was observed on the 20th day after delivery, but this was initially misdiagnosed as bladder prolapse before being later corrected to a diagnosis of vaginal prolapse of submucosal uterine leiomyoma. Due to the prompt use of powerful antibiotics and transvaginal myomectomy, the patient was able to avoid hysterectomy and preserve fertility. For parturient women with hysteromyoma and recurrent fever after delivery where the source of infection cannot be found, the infection of the submucous leiomyoma of the uterus should be highly suspected. Imaging examination can be of great diagnostic help. Transvaginal myomectomy should be the first choice for treating prolapsed leiomyoma in cases where there is no obvious blood supply or if pedicle can be achieved.